Women in management threat or opportunity - CRM Educational Films (Del Mar, Calif. : CRM/McGraw-Hill Films, 1975)
This video examines the effects of the women's liberation movement in several different organizations and then shows the many ways- both good and bad- that leaders are dealing with situation
Keywords: Women -- Employment